2018
DOI: 10.3390/ma11020272
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and Corresponding Quenching Efficiency of Fluorescent DNA Probes

Abstract: Based on the fluorescence resonance energy transfer (FRET) mechanism, fluorescent DNA probes were prepared with a novel DNA hairpin template method, with SiO2 coated CdTe (CdTe/SiO2) core/shell nanoparticles used as the fluorescence energy donors and gold (Au) nanoparticles (AuNPs) as the energy acceptors. The nanostructure and energy donor/acceptor ratio in a probe were controlled with this method. The relationship between the nanostructure of the probes and FRET efficiency (quenching efficiency) were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The energy-transfer efficiencies indicate that PL quenching takes place by nonradiative energy transfer, and also that this quenching is incomplete, leaving some emission to be detected. Gold nanoparticles are known to be efficient quenchers for luminophores very close to their surface, and the mechanism for this quenching has been attributed to either FRET or NSET mechanism. ,,, We therefore subjected our PL decay time results to both FRET and NSET theory with the aim of contributing to the understanding of the energy-transfer processes in assemblies of photoluminescent entities and plasmonic nanoparticles, particularly to find out which theory, FRET or NSET, makes the best predictions about energy transfer in these systems. The long-lived PL emission from Tb enables a clear distinction of Tb from other short-lived background PL while still being subject to electric dipole–dipole energy transfer …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy-transfer efficiencies indicate that PL quenching takes place by nonradiative energy transfer, and also that this quenching is incomplete, leaving some emission to be detected. Gold nanoparticles are known to be efficient quenchers for luminophores very close to their surface, and the mechanism for this quenching has been attributed to either FRET or NSET mechanism. ,,, We therefore subjected our PL decay time results to both FRET and NSET theory with the aim of contributing to the understanding of the energy-transfer processes in assemblies of photoluminescent entities and plasmonic nanoparticles, particularly to find out which theory, FRET or NSET, makes the best predictions about energy transfer in these systems. The long-lived PL emission from Tb enables a clear distinction of Tb from other short-lived background PL while still being subject to electric dipole–dipole energy transfer …”
Section: Resultsmentioning
confidence: 99%
“…Similar to FRET, NSET is a nonradiative dipole–dipole energy transfer, but in contrast to FRET (in which both donor and acceptor are considered as point dipoles), the acceptor is a nanometric surface modeled as a collection of many dipoles. In NSET, the efficiency is inversely proportional to the fourth power of the distance between the donor and the acceptor surface of a metallic nanoparticle (NP) (in most cases AuNPs). , Research showed that NSET model was in good agreement with the experimental data on small-size AuNPs (below 3 nm) in combination with organic dyes and quantum dots (QDs) as donors. NSET behavior with energy-transfer efficiencies independent of the NP size or number of donors was also demonstrated for larger-size AuNPs. However, in other studies reporting about biosensors that use photoluminescence (PL) quenching by AuNPs, the underlying energy-transfer mechanism is assumed to be FRET, , or is not specified. , …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…40 An NSET-based biosensing platform between SiO 2 coated CdTe (CdTe/SiO 2 ) core/shell NPs and AuNPs was also reported for the same aim, facilitating facile and sensitive detection of DNA. 41 Furthermore, an effective fluorescence quenching of rhodamine 6G was achieved by Patel et al 42 using rhodamine 6G and AuNPs as NSET pairs. In this assay, DNA-modified AuNPs act as an acceptor of fluorescence emitted by the rhodamine 6G compound.…”
Section: Resultsmentioning
confidence: 99%
“…We note here that AuNPs are known to be efficient quenchers for the nearby fluorophores, 24,87 and the quenching mechanism is attributed to either the FRET or NSET mechanism. 23,36,[88][89][90][91] Therefore, it is important to find out which model, FRET or NSET, is appropriate for the present excitation energy transfer from F-AgAu to AuNPs in this work. The FRET model is based on the non-radiative dipole-dipole interaction between two molecular dyes having a separation distance of up to 10 nm.…”
Section: Mechanism Of Energy Transfer From F-agau To Aunpsmentioning
confidence: 99%